Pengaruh lama gliserolisasi terhadap keberhasilan produksi semen beku Sapi Simmental - Sudarmanto Sudarmanto; Trinil Susilawati; Nurul Isnaini (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The purpose of this research was to determine duration effect of different glicerolitation time on the quality and frozen semen production of Simmental bulls in Ungaran Artificial Insemination Center. The materials of the research used four Simmental bulls. The method of the study used experimental laboratory. There were two treatments in the study (P0 = duration of glicerolitation for > 3 hours, P1 = duration of gliserolitation for 15 minutes) and four Simmental bulls. The research parameter included semen volume, pH, concentration of spermatozoa, frozen semen production and post thawing motility from 8 treatments. Data were analyzed using t-test. The quality of fresh semen had average percentage of motility 70% and 2+. The research showed that the frozen semen production during 15 minutes of glicerolitation was better than that of >3 hour duration. Moreover, the motile sperms produced during 15 minutes of glicerolitation was higher than those which produced during >3 hours of glicerolitation. Keywords: motility, glicerolitation, frozen semen